THE SCHOOL ROLE IN THE EFFORT OF EMPOWERING IN EARLY CHILDHOOD ENVIRONMENT - Pertiwi, Eky Prasetya; Zahro, Ianatuz; Fadli, Ahmad (Jurnal AUDI: Jurnal Ilmiah Kajian Ilmu Anak dan Media Informasi PAUD, 2025)
The objective of this research was to find out how the school role in the effort of empowering society in the early childhood education environment. The approach of this research used a qualitative research method, the data obtained were then analyzed qualitatively, which the scope of the research was at TK PAUD Lab-school Jember. Based on the results of the study found that: (1) the School role in the effort of empowering society in early childhood education Lab-school environment is by carrying out good communication, this role can be done by several related parties; including teachers and school principals, school committees, and the community in the school environment. Their roles that shall do: (a) Teachers and school principals; provide decisions or policies, stimulation to students’ guardians and support. (b) The school committees and classroom teacher; coordinate, cooperate, and carry out a joint decision. (c) Local community; participate and give support in every activity. (2) Some of the obstacle factors in empowering the community in the PAUD Lab School include: (a) The school itself; limited facilities and infrastructure, (b) The school environment: The economic condition, the student-parent activities, and lots of activities competition in larger communities. Abstrak Tujuan penelitian ini adalah untuk mengetahui bagaimana peran sekolah dalam upaya pemberdayaan masyarakat di lingkungan PAUD. Pendekatan penelitian ini menggunakan metode penelitian kualitatif, data yang diperoleh kemudian dianalisis secara kualitatif yang ruang lingkup penelitiannya di TK PAUD Lab-sekolah Jember. Berdasarkan hasil penelitian ditemukan bahwa: (1) Peran sekolah dalam upaya pemberdayaan masyarakat PAUD di lingkungan sekolah Lab-sekolah adalah dengan melaksanakan komunikasi yang baik, peran tersebut dapat dilakukan oleh beberapa pihak terkait; termasuk guru dan kepala sekolah, komite sekolah, dan masyarakat di lingkungan sekolah. Peran mereka yang harus: (a) Guru dan kepala sekolah; memberikan keputusan atau kebijakan, stimulasi kepada wali dan dukungan siswa. (b) Komite sekolah dan guru kelas; berkoordinasi, bekerja sama, dan melaksanakan keputusan bersama. (c) Komunitas lokal; berpartisipasi dan memberikan dukungan dalam setiap kegiatan. (2) Beberapa faktor penghambat pemberdayaan masyarakat di Sekolah Lab PAUD antara lain: (a) Sekolah itu sendiri; Terbatasnya sarana dan prasarana, (b) Lingkungan sekolah: Kondisi ekonomi, kegiatan orang tua murid, dan banyaknya persaingan kegiatan di masyarakat yang lebih luas.